Short telomere length, lung function and chronic obstructive pulmonary disease in 46 396 individuals. Issue 5 (25th December 2012) - Rode, Line; Bojesen, Stig E; Weischer, Maren; Vestbo, Jørgen; Nordestgaard, Børge G
Abstract : Background: A previous case–control study of 100 individuals found that short telomere length was associated with a 28-fold increased risk of chronic obstructive pulmonary disease (COPD). Objectives: To test the hypothesis that short telomere length is associated with reduced lung function and an increased risk of COPD. Methods: Observational study of 46 396 individuals from the Danish general population. Measurements: Leucocyte telomere length and spirometry were measured. COPD was defined using either fixed forced expiratory volume in 1 s (FEV1 )/forced vital capacity (FVC) ratio <0.70 as suggested by the Global initiative for chronic Obstructive Lung Disease (GOLD) or FEV1 /FVC below the lower limit of normal (LLN). Results: Telomere length decreased significantly with increasing age (p<10 −300 ). FEV1, FVC and FEV1 /FVC decreased with decreasing telomere length quartiles (p trend: 5×10 −51, 5×10 −35 and 6×10 −137, respectively), but the associations attenuated after age and multivariable adjustment. The risk of COPD increased with decreasing telomere length quartile (p trend: p=7×10 −92 for GOLD; p=8×10 −44 for FEV1 /FVC below LLN), but associations also attenuated after adjustment. Unadjusted and multivariable adjusted OR for shortest versus longest telomere length quartiles were 2.06 (95% CI 1.91 to 2.22) and 1.15 (95% CI 1.06 to 1.25) for GOLD and 1.73 (95% CI 1.60 to 1.88) and 1.19 (95% CI 1.09 to 1.30) for FEV1 /FVC below LLN, respectively. Per 1000 base pairs decrease in telomere length, the multivariable adjusted OR was 1.07 (95% CI 1.03 to 1.10) for GOLD and 1.07 (95% CI 1.03 to 1.11) for FEV1 /FVC below LLN. Conclusions: Short telomere length is associated with decreased lung function and with increased risk of COPD, but the associations are markedly attenuated after adjustment. Our data support a modest correlation between telomere length and the lung function indices examined.